Synthesis, characterization and mechanical properties of biodegradable magnesium alloys. Issue 1 (February 2013) - Gill, Puneet; Munroe, Norman; Datye, Amit
Abstract : Metallic materials continue to play an essential role as biomaterials to assist with the repair or replacement of various diseased or damaged parts of an anatomy. Currently approved and commonly used metallic biomaterials, such as stainless steel, titanium, cobalt, chromium and other alloys, are found to have adverse effects leading, in some cases, to mechanical failure and rejection of the implant. The physical or chemical nature of the degradation products of some implants initiates an adverse foreign body reaction in tissue. Some metallic implants remain as permanent fixtures, whereas others such as plates, screws and pins that are used to secure serious fractures are removed by a second surgical procedure after the tissue has healed sufficiently. Repeat surgical procedures increase the cost of health care and the possibility of patient morbidity. The concept of magnesium as a biodegradable implant was first investigated 100 years ago by Payr as an innovative approach to address the aforementioned concerns. In this investigation, three alloys were fabricated by casting technology: Magnesium-Zinc (MgZn), Magnesium-Zinc-Calcium (MgZnCa) and Magnesium-Zinc-Calcium-Gadolinium (MgZnCaGd). The alloys were subjected to metallographic characterization by scanning electron microscopy (SEM) and X-ray diffraction (XRD). SEM analysis depicted precipitates; some of which occurred along the grain boundaries, whereas XRD depicted the formation of Laves phases. The mechanical properties and surface energy were also determined. Improved mechanical properties were observed with the addition of alloying elements.